2020
DOI: 10.1038/s41392-020-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

PIM kinase inhibition: co-targeted therapeutic approaches in prostate cancer

Abstract: PIM kinases have been shown to play a role in prostate cancer development and progression, as well as in some of the hallmarks of cancer, especially proliferation and apoptosis. Their upregulation in prostate cancer has been correlated with decreased patient overall survival and therapy resistance. Initial efforts to inhibit PIM with monotherapies have been hampered by compensatory upregulation of other pathways and drug toxicity, and as such, it has been suggested that co-targeting PIM with other treatment ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 139 publications
(212 reference statements)
3
51
0
Order By: Relevance
“…Inducing Pim1 with DOX in this tumor cell line caused an increase in EDC3 phosphorylation (Fig 3C). This increase was similar to that of the ribosomal protein S6, which is a downstream target of Pim regulation of mTORC1 (Zhang et al , 2009; Padi et al , 2019; Luszczak et al , 2020). The addition of Pim447 to these cells reversed the effect of Pim1 overexpression, eliminating phosphorylation.…”
Section: Resultssupporting
confidence: 53%
“…Inducing Pim1 with DOX in this tumor cell line caused an increase in EDC3 phosphorylation (Fig 3C). This increase was similar to that of the ribosomal protein S6, which is a downstream target of Pim regulation of mTORC1 (Zhang et al , 2009; Padi et al , 2019; Luszczak et al , 2020). The addition of Pim447 to these cells reversed the effect of Pim1 overexpression, eliminating phosphorylation.…”
Section: Resultssupporting
confidence: 53%
“…The PIM and PI3K/mTOR pathways are interconnected, with each pathway influencing the signalling and activity of the other 12 . There is a significant overlap of cellular functions of PIM and AKT 6 .…”
Section: Introductionmentioning
confidence: 99%
“…c-MYC is also upregulated by both PIM and mTOR 6 . This relationship gives rise to the development of resistance to treatment, as the pathways can bypass the inhibition by compensating for loss of signalling of either one 12 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Preclinical studies revealed biological pathways implicated in tumorigenesis and therapy resistance, such as NF-kB, PI3K/mTOR, and WNT/β-catenin. 6 9 However, in preclinical studies, cell culture of primary osteosarcoma cells or cell lines undergo extensive genetic changes and lose their phenotypic heterogeneity; thus, the conclusions from studies made with these cells are different from those of the primary tumors. Single-cell transcriptomics technologies can reveal cellular heterogeneity within a cell population.…”
Section: Introductionmentioning
confidence: 99%